Role of Dexamethasone in Prevention of Pain Flares in Painful Bone Metastases after Radiotherapy - Sunder Singh; Rakesh Dhankhar; Kiran Dahiya (Recent Developments in Medicine and Medical Research Vol. 16, 2021)
Metastatic bone disease is a common problem observed in oncology practice. In solid tumors, bone is a common site of metastases. In advanced cancer, bones are the third most common site of metastases after liver and lungs. The common primary sites causing bone metastases are breast, lung and prostate, urinary bladder, uterus, kidney, melanoma and thyroid. Metastases in skeletal are usually multiple, solitary metastases are observed only in 10% cases. Bone metastases cause pain directly through local invasion and indirectly through alteration of the remodelling activity of osteoblasts and osteoclasts. Radiotherapy is the most effective treatment for bone metastases.Pain flare is a common phenomenon in patients receiving palliative radiotherapy. Dexamethasone is a long acting steroid which has shown effectiveness in prevention of pain flare. The main objective of the study is to determine the role of dexamethasone in prevention of pain flares in painful bone metastases after radiotherapy.